2020
DOI: 10.1002/hed.26499
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node characteristics and their prognostic significance in oral squamous cell carcinoma

Abstract: Background: The prognostic significance of various histopathologic lymph node-based biomarkers in oral squamous cell carcinoma (OSCC) needs further evaluation. Methods: Retrospective analysis of 212 OSCC patients with regional metastasis to determine the association of extranodal extension (ENE), extent of ENE, size of metastatic deposit, lymph node yield (LNY), lymph node ratio (LNR), and topography of involvement with survival outcomes. Results: The presence of ENE, larger nodal deposit, higher pN stage, lym… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 36 publications
1
43
0
Order By: Relevance
“…The limitations of our work include the retrospective design and the limited number of patients; we also cannot recommend a clinical LNR cutoff that usefully identifies patients who might benefit from more intensive adjuvant therapy. Prospective studies and further considerations on various histopathologic lymph node‐based biomarkers are required 34–36 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The limitations of our work include the retrospective design and the limited number of patients; we also cannot recommend a clinical LNR cutoff that usefully identifies patients who might benefit from more intensive adjuvant therapy. Prospective studies and further considerations on various histopathologic lymph node‐based biomarkers are required 34–36 …”
Section: Discussionmentioning
confidence: 99%
“…Prospective studies and further considerations on various histopathologic lymph node-based biomarkers are required. [34][35][36] Lymph node status is the principal prognostic indicator of both OS and DFS in patients with OSCC. Many reports have shown that the LNR predicts survival.…”
Section: Lower Gingiva 18mentioning
confidence: 99%
“…90%) show 5 mm or less of extension beyond the capsule, and the average extent is typically around 2 mm. 37,38 Evidence is emerging that 2 mm may be an important cutoff point, but data are limited and conflicting. Wreesmann et al 39 used receiver operating characteristics curve analysis to determine that 1.7 mm or less of extranodal extension had the same disease-specific survival as no extranodal extension in oral cavity SCC, whereas those with more than 1.7 mm of extranodal extension fared worse, including in multivariate analysis.…”
Section: Figure 1 Lymph Node Metastases Without Pathologic Extranodal Extensionmentioning
confidence: 99%
“…ENE features can be found in metastatic nodes of different sizes and different levels of invasion and in OCSCC patients with either primary or recurrent lesions 24 . Although patients with ENE nodes would most likely receive augmented treatment regimens, the outcomes available in the literature were vastly different, showing varying treatment benefits among OCSCC patients 25 - 27 . As was shown in our study, those with unilateral ENE nodes enjoyed much better DFS results than those with bilateral ones.…”
Section: Discussionmentioning
confidence: 99%
“…Some even asserted that more than 2 ENE nodes would confer unfavorable prognoses, while single ENE nodes did not affect overall survival 21 . Others considered that the unfavorable distributions (lower levels) of multiple ENE nodes would constitute risk factors 27 , 33 . However, the MLN burden with bilateral ENE features might have strong relations to an inferior DFS, as demonstrated in our study.…”
Section: Discussionmentioning
confidence: 99%